Determinants of Previous HIV Testing and Knowledge of Partner's HIV Status Among Men Attending a Voluntary Counseling and Testing Clinic in Dar es Salaam, Tanzania. (November 2013) - Conserve, Donaldson; Sevilla, Luis; Mbwambo, Jessie; King, Gary
Voluntary Counseling and Testing (VCT) remains low among men in sub-Saharan Africa. The factors associated with previous HIV testing and knowledge of partner's HIV status are described for 9, 107 men who visited the Muhimbili University College of Health Sciences' VCT site in Dar es Salaam, Tanzania, between 1997 and 2008. Data are from intake forms administered to clients seeking VCT services. Most of the men (64.5%) had not previously been tested and 75% were unaware of their partner's HIV status. Multivariate logistic regression revealed that age, education, condom use, and knowledge of partner's HIV status were significant predictors of previous HIV testing. Education, number of sexual partners, and condom use were also associated with knowledge of partner's HIV status. The low rate of VCT use among men underscores the need for more intensive initiatives to target men and remove the barriers that prevent HIV disclosure.